2002
DOI: 10.1046/j.1365-263x.2002.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between asthma and dental erosion? A case control study

Abstract: There were significant differences in the prevalence of erosion between the three groups, children with asthma having a higher prevalence than the control group. Although there was a relationship between the levels of erosion and some medical history and acidic dietary components, these did not explain the higher levels in asthmatic children. Further investigation is required into the factors affecting the increased prevalence of erosion in children with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 29 publications
3
51
1
3
Order By: Relevance
“…Some studies have found a higher incidence of erosion in asthmatics. [23][24][25][26] In contrast, other studies did not find the same correlation. 27 So till now, the evidence for such an association is unclear.…”
Section: Distribution Of Dental Erosionmentioning
confidence: 91%
“…Some studies have found a higher incidence of erosion in asthmatics. [23][24][25][26] In contrast, other studies did not find the same correlation. 27 So till now, the evidence for such an association is unclear.…”
Section: Distribution Of Dental Erosionmentioning
confidence: 91%
“…Such parameters include salivary pH, buffering capacity, calcium and phosphate content, citrate content, pyrophosphate content, mucin content and unstimulated and stimulated flow rates (Mannerberg, 1963). Associations between unstimulated salivary flow rate and buffering capacity with dental erosion have been reported (Hellström, 1977;Woltgens et al, 1985;Bevenius & l'Estrange, 1990;Järvinen et al, 1991;Gudmundsson et al, 1995), although such associations were not observed in patients with reflux disease (Meurman et al, 1994) or in a recent case-control study of children (Al-Dlaigan et al, 2002). Nevertheless, both salivary flow and buffering capacity appear to be important in neutralising dietary acid as demonstrated by the restoration of resting pH at the tooth surface within a few minutes of acid consumption (Millward et al, 1997).…”
Section: Dental Disease and Salivary Factorsmentioning
confidence: 97%
“…16,17 Birçok çalışma astımın dental erozyon riskini arttırdığını bildirse de, 5,18,19 Dugmore ve Rock 20 astım ve dental erozyon arasında bir ilişki saptamamışlardır. Toz inhaler kullanan bireylerin erozyon riskine karşı, inhaleri kullandıktan hemen sonra likid antiasitler, karbonatlı su, süt veya nötral sodyum floridli gargaralarla ağızlarını çalkalamaları önerilmelidir.…”
Section: Astım Ve Dental Erozyonunclassified